REALIGNING INDONESIAN WASTE-TO-ENERGY POLICIES WITH SDG 11: ANALYSIS OF LEGAL COMPLIANCE AND ITS IMPLICATIONS - Sudirman, Lu; Hutauruk, Rufinus Hotmaulana; Alhakim, Abdurrakhman; Tan, Winsherly (Jurnal Pembaharuan Hukum, 2024)
To date, Indonesia is still grappling with waste management issues, which is a significant obstacle to realizing Sustainable Development Goals (SDG) 11. One of the ways to deal with this issue is through the development of the waste-to-energy (WtE) system, which can be utilized to transform waste into precious energy resources. However, this system must also be supported with robust legal compliance to ensure that its development is not solely focused on generating profits through energy production but also meets its noble purpose of improving sustainability as conceptualized within SDG 11. This study utilizes the normative legal research method, along with a statutory approach. Analysis of this study finds that the current Indonesian legal framework is insufficient in providing a robust mechanism of compliance to ensure that the waste-to-energy system can contribute to the broader waste-management issues and their ramifications, specifically due to the lack of recognition of the unique intricacies of the development of WtE systems, along with the lack of normative implementation of SDG 11. The paper proposes a model of normative construction to cover these issues as a way of ensuring growth and environmental sustainability in Indonesia, particularly regarding waste management.